Gene expression profiles of CD4/CD8 double‐positive T cells in porcine peripheral blood. (8th May 2018) - Okutani, Mie; Tsukahara, Takamitsu; Kato, Yoshihiro; Fukuta, Kikuto; Inoue, Ryo
Abstract: A characteristic subset of T cells, known as double positive T cells (DPTC) and expressing both cluster of differentiation 4 (CD4) and CD8, is observed in porcine peripheral blood. Previous studies suggested that DPTC might be memory cells. However, detailed phenotypes and functions of DPTC are yet to be fully elucidated and thus, the relatedness of DPTC with memory phenotypes remains unclear. In this study, DPTC gene expression profiles in peripheral blood were analyzed by DNA microarray in Experiment 1 and compared with those of CD4 single positive T cells (4SPTC) and CD8 single positive T cells (8SPTC). Expressions of IFNG, CCL5, NCK2, CCR2 and ITGB1 were higher than that of 4SPTC and 8SPTC. In contrast, expressions of CCR7 and SELL were lower than that of 4SPTC and 8SPTC. These results suggested that DPTC were either effector T cells or effector memory T cells (TEM ). Next, to determine whether DPTC were effector T cells or TEM, differences in the response of DPTC and 8SPTC against immunized/primed antigens were compared (Experiment 2). While DPTC showed quick elevation of IL2 and CD25 gene expressions against in vitro stimulation of primed/immunized antigens, 8SPTC did not. These results suggest that at least some DPTC likely belong to TEM .